Millennials as the Future of Corrections: A Generational Analysis of Public Policy Opinions - Lee, Heejin (Crime & delinquency, 2022)
This study presents a comprehensive assessment of what Millennials think about U.S. correctional policy. Using a 2017 national-level sample (N?=?1,000), Millennials? correctional policy opinions across 13 outcomes are assessed and compared to the views of other generations. The main findings are twofold. First, Millennials are only modestly punitive but clearly supportive of progressive policies. Thus, Millennials favor a rehabilitative correctional orientation, believe in offender redeemability, and prefer policies to protect ex-felons? civil rights and to expunge criminal records for minor offenses. Second, generational differences in public support for correctional policies are mostly limited. Americans of all generations tend to endorse inclusionary policies?a finding indicating that the future of American corrections might see a lengthy era of progressive reform.